2018
DOI: 10.1111/cdev.13132
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self‐Reported Well‐Being: A Follow‐Up Study of Children Aged 12–14 in Algeria

Abstract: This article reports on a 2-year follow-up study (443 Algerian children). Using a variety of satisfaction measures, along with detailed questions relating to family, school, local area, material deprivation, and daily activities, we aim to explore changes in the self-reported well-being of children from age 12 to 14. Satisfaction with health and friends remained stable, meanwhile satisfaction with school decreased more for boys than for girls, but satisfaction with family, time use, and material possessions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
11
2
2
Order By: Relevance
“…A declining-with-age trend is perhaps the dominant finding in the literature, and has been reported in early cross-sectional studies from Israel (Ullman & Tatar, 2001), South Korea (Park et al, 2005), Romania and Spain (Casas et al, 2013) and Germany (Goldbeck et al, Pg. 6 2007) and more recent longitudinal studies from Spain (Aymerich et al, 2021;González-Carrasco et al, 2017;González-Carrasco, Sáez, & Casas, 2020), Hong Kong (Shek & Liang, 2018), and Algeria (Tiliouine, Rees, & Mokaddem, 2019). However, a cross-sectional study in the US did not find a change in life satisfaction across grades 9-12 (Huebner et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…A declining-with-age trend is perhaps the dominant finding in the literature, and has been reported in early cross-sectional studies from Israel (Ullman & Tatar, 2001), South Korea (Park et al, 2005), Romania and Spain (Casas et al, 2013) and Germany (Goldbeck et al, Pg. 6 2007) and more recent longitudinal studies from Spain (Aymerich et al, 2021;González-Carrasco et al, 2017;González-Carrasco, Sáez, & Casas, 2020), Hong Kong (Shek & Liang, 2018), and Algeria (Tiliouine, Rees, & Mokaddem, 2019). However, a cross-sectional study in the US did not find a change in life satisfaction across grades 9-12 (Huebner et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, data are more controversial about differences in subjective well-being between boys and girls. Some studies showed a higher level of subjective well-being for boys [50,56], and some showed a higher level of subjective well-being for girls [55][56][57]. In a study by Goldbeck and colleagues, girls showed a lower level of overall life satisfaction and satisfaction with their health, than boys [50].…”
Section: Subjective Well-being For Different Gendermentioning
confidence: 99%
“…Интересно, что гендерные различия появляются после того, как на чинает снижаться уровень удовлетворенности, а снижение для девочек более Т. Н. Канонир, А. А. Куликова, Е. А. Орел СОЦИОЛОГИЯ ОБРАЗОВАНИЯ выраженное [Michel et al, 2009;González Carrasco et al, 2017]. Лонгитюдное исследование в Алжире показывает различия в пользу девочек по шкалам удо влетворенности школой [Tiliouine, Rees, Mokaddem, 2019]. В этом же исследова нии не наблюдаются гендерные различия в уровне удовлетворенности друзьями [ibidem], несмотря на то что они фиксировались в возрасте восьми лет, когда девочки показывали более высокий уровень удовлетворенности своими отно шениями со сверстниками, чем мальчики [Michel et al, 2009].…”
Section: субъективное благополучие у детей и подростков: гендерные раunclassified
“…В последующих исследованиях важно отслеживать изменения уровня благополучия девочек и мальчиков, так как, возможно, уровень благополучия девочек при переходе в подростковый возраст может существенно понизиться в сравнении с мальчи ками, что в основном связывают с более острым переживанием физиологиче ских и гормональных изменений, происходящих в пубертатный период у девочек [Goldbeck et al, 2007;Michel et al, 2009]. Мальчики и девочки не показали раз личий в уровне сотрудничества с одноклассниками ни в третьем, ни в четвертом классе, a уровень враждебности в отношениях с одноклассниками у девочек существенно ниже, чем у мальчиков как в третьем, так и в четвертом классе, что согласуется с предыдущими исследованиями детей более старшего возраста [Tiliouine, Rees, Mokaddem, 2019].…”
Section: результатыunclassified